S111 The role of TNF-related apoptosis inducing ligand (TRAIL) in pulmonary fibrosis. (2nd December 2011) - McGrath, E E; Lawrie, A; Marriott, H; Mercer, P F; Cross, S S; Chambers, R C; Dockrell, D H; Whyte, M K B
Abstract : Introduction: The concept of driving cellular apoptosis as a potential therapy for diseases characterised by inappropriate cellular persistence or proliferation is of widespread interest. We previously showed a death receptor ligand, TRAIL, accelerates neutrophil apoptosis without associated cell activation ( J Immunol 170 :1027–33) and other work revealed TRAIL-induced apoptosis of human lung fibroblasts. The aims of this project were to study the role of TRAIL in a bleomycin lung injury model in wild-type and TRAIL−/− mice and in patients with idiopathic pulmonary fibrosis (IPF). Methods: Mice received intratracheal bleomycin or saline control. Bronchoalveolar lavage (BAL) at 3, 7, 16 and 23 days was analysed by cytospin morphology and haemocytometer count for % neutrophils, % neutrophil apoptosis, total number of neutrophils and total number of apoptotic cells. Flow cytometry was also used to analyse apoptosis. Collagen deposition in whole lung samples was analysed using a hydroxyproline assay. TRAIL expression and TUNEL positive events were also analysed. Serum and lung tissue from IPF patients/controls were examined for TRAIL expression and concentration. Lung function and survival data were retrieved from patient charts. Results: BAL analysis revealed statistically significant differences between TRAIL−/− and wild-type mice, with TRAIL−/− mice showing increased neutrophil numbers and reduced neutrophil apoptosis as absolute count or as % total cell count. Collagen deposition was statistically greater in TRAIL−/− mice at 16 days. At day 23, TRAIL−/− mice had decreased TUNEL positive events compared to wild-type mice. Histological analysis of murine lung sections revealed specific TRAIL expression in bronchus associated lymphoid tissue and alveolar macrophages. IPF patient lung section analysis revealed an absence of TRAIL expression compared to controls. IPF patients had significantly lower serum levels of TRAIL than controls which inversely correlated with TLCO (% predicted) and positively correlated with survival from diagnosis. Conclusions: We demonstrated that the neutrophilic inflammatory response to bleomycin is increased in TRAIL−/− compared with wild-type mice and that this finding is associated with increased collagen deposition. We also demonstrated reduced pulmonary and systemic expression of TRAIL in IPF, which correlates with worse pulmonary function and clinical outcome. This data suggests TRAIL may have biomarker potential and therapeutic benefit in pulmonary fibrosis.